2020
DOI: 10.1101/2020.04.23.20072215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatio-temporal associations between deforestation and malaria incidence in Lao PDR

Abstract: As countries in the Greater Mekong Sub-region (GMS) increasingly focus their malaria control and elimination efforts on forest-going populations, greater understanding of the relationship between deforestation and malaria incidence will be essential for programs to assess and meet their 2030 elimination goals. Leveraging village-level health facility surveillance data and forest cover data in a spatio-temporal modeling framework, we found evidence that deforestation is associated with short-term increases, but… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The clusters of transmission identified in this study were consistent with previous findings indicating that the at-risk group primarily consisted of male adults who spent the night in the forest, with their activities centered around villages located near the forest [14]. Adding precision to this general finding, we noted that the majority of potential transmission links were temporally related and spatially concentrated within a 20-kilometer radius on both the east and west sides of the Pathoomphone district, an area previously noted to have high levels of forested and agricultural activities [7]. In addition, we also detected a few crossdistrict transmission links between the Pathoomphone and Moonlapamok districts, which may be attributed to mobility patterns observed among the forest-goer population.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The clusters of transmission identified in this study were consistent with previous findings indicating that the at-risk group primarily consisted of male adults who spent the night in the forest, with their activities centered around villages located near the forest [14]. Adding precision to this general finding, we noted that the majority of potential transmission links were temporally related and spatially concentrated within a 20-kilometer radius on both the east and west sides of the Pathoomphone district, an area previously noted to have high levels of forested and agricultural activities [7]. In addition, we also detected a few crossdistrict transmission links between the Pathoomphone and Moonlapamok districts, which may be attributed to mobility patterns observed among the forest-goer population.…”
Section: Discussionsupporting
confidence: 84%
“…In northern Lao PDR, malaria transmission is very low, with a predominance of Plasmodium vivax infections. In contrast, southern Lao PDR bears over 90% of the nationwide malaria disease burden with coendemic transmission of both Plasmodium falciparum and Plasmodium vivax [6,7]. The higher malaria burden observed in southern Lao PDR can be attributed to several factors.…”
Section: Introductionmentioning
confidence: 99%
“…As "forest malaria" is a major contributor to residual malaria incidence, 85,86 deforestation and landscape changes will have a significant impact on vector ecology and malaria transmission. 87 Our study conducted in the China-Myanmar border area showed that adult An. sinensis and An.…”
Section: Mosquito Ecology and Insecticide Resistancementioning
confidence: 85%
“…Now, in eLife, François Rerolle (University of California San Francisco; UCSF) and colleagues report new conclusions based on unprecedented data from the Lao People’s Democratic Republic (Lao PDR) in the Greater Mekong Subregion, where countries are increasingly trying to control forest malaria ( Rerolle et al, 2021 ). The team applied a spatio-temporal statistical model to a dataset formed of longitudinal records of malaria cases in individual villages, combined with high-resolution images of forest cover obtained through remote sensing.…”
mentioning
confidence: 99%